Ancient Kanesh - Larsen, Mogens Trolle, 1937- (New York)
xii, 330
Keywords: "The ancient Anatolian city of Kanesh (present-day Kültepe, Turkey) was a continuously inhabited site from the early Bronze Age through Roman times. The city flourished c.2000–1750 BCE as an Old Assyrian trade outpost and the earliest attested commercial society in world history. More than 23,000 elaborate clay tablets from private merchant houses provide a detailed description of a system of long-distance trade that reached from central Asia to the Black Sea region and the Aegean. The texts record common activities such as trade between Kanesh and the city state of Assur and between Assyrian merchants and local people. The tablets tell us about the economy as well as culture, language, religion, and private lives of individuals we can identify by name, occupation, and sometimes even personality. This book presents an in-depth account of this vibrant Bronze Age Anatolian society, revealing the daily lives of its inhabitants." --